Cover Image, Volume 39, Issue 6. Issue 6 (16th October 2019) - Sun, Xin; Yan, Peiyi; Zou, Chang; Wong, Yin‐Kwan; Shu, Yuhan; Lee, Yew Mun; Zhang, Chongjing; Yang, Nai‐Di; Wang, Jigang; Zhang, Jianbin
Abstract : Description of the front cover image : The cover image is based on the REVIEW ARTICLE Targeting autophagy enhances the anticancer effect of artemisinin and its derivatives by Xin Sun et al., https://doi.org/10.1002/med.21580 . Credit : Cover image © Jianbin Zhang and Jigang Wang.